Alarm system using Microcontroller , GPS and GSM devices - Nadia Mahmood Hussein; Saad Najim AlSaad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
During last ten years, it is noticed an increasing number of accidents causing losing of large number of victims This paper related to an explosion alarm system to inform the emergency center to make fast response for saving and rescuing life of people. The whole system is controlled by arduino uno microcontroller unit which senesces the environment and gives reaction based on what it sensed. Also GPS (global Position System) is used that gives the latitude and longitude of the event and sends this information as a short message to GSM (Global System for Mobile Communication) mobile using SMS (Short Message Service) . In other side, database of location (latitude, longitude) of each help center place is saved to be used for determining the nearest center to the accident through shortest path formula. Finally the path between emergency center and accident location is tracked through Google map application.